Computerization and the Decline of American Unions: Is Computerization Class-Biased?. Issue 4 (November 2019) - Kristal, Tali
This article offers a new explanation for union decline by focusing on a currently neglected site that exemplifies the fragility of unions—the shop floor in the computer revolution era. Using data from several sources including the National Labor Relations Board, it analyzes the effect of using a computer at work on the odds of being a union member and the broader effect of computerization on union strength within detailed industries between 1973 and 2002. Workers who used a computer at work were found less likely to be union members, and computerization of workplaces accounted for about a quarter of the decline in union density within industries; partly by changing the skill composition of industries' workforces and partly by enhancing employers' resistance to unions as measured by their use of unfair labor practices and decertification elections as documented by the National Labor Relations Board. The findings are explained in a new theoretical framework that specifies what computerization does to unions by (a) reshaping the way products are made and services are provided and (b) boosting a profound power shift throughout workplaces.